Risk Management Analysis of Third Construction Stage in Diagnostic and Cardiac Center Building at Dr. Hasan Sadikin General Hospital (The Indonesian Journal of Business Administration, 2013)
Dr. Hasan Sadikin General Hospital (HSGH) is a teaching hospital as well as a tertiary referral hospital for West Java province. To support this role, HSGH is required to be capable of providing a high quality health services corresponding to the demands of society. Following this, the development of Diagnostic and Cardiac Center Building are being carried out. However, it should be consider that there are risks that could arise at anytime in the future, along with the development of Diagnostic and Cardiac Center. Risk management analysis of Diagnostic and Cardiac Center Building done firstly through risk identification. Secondly is risk measurement. Lastly, the recommendation of risk response planning for HSGH. The identitified risks in third construction stage is 36 risks with the majority classified in moderate and high risk. Furthermore, for risk response planning there are four strategy namely acceptance, mitigation, risk transfer, and avoidance. The proposed risk response planning for risk associated with third construction stage mainly using risk transfer strategy.Â Keywords: Risk Management, Risk Identification, Risk Response Planning